Richard Hurrell Froude et le spectre du désétablissement - Hervé Picton (Cahiers Victoriens et Edouardiens)
In the early 1830s, the Church’s authority is undermined by a host of scandals widely relayed by the press. The bishops’ vote against the Reform Bill had further alienated public opinion. The repeal of the Test and Corporations Act (1828), the Catholic Emancipation Act (1829) and the Irish Church Bill (1833) also weakened the Church’s central position in the life of the nation. The Radicals and the Dissenters called for disestablishment, while the Whigs envisaged a radical reform of the Church. If the vast majority of the clergy staunchly opposed disestablishment, Tractarian leaders generally thought the Church would benefit from it. The most vocal and systematic supporter of disestablishment was Hurrell Froude who, in « Remarks on State Interference in Matters spiritual » (1833), argues that if the establishment was justified under Elizabeth’s reign (when Parliament was a lay synod of the Church), it is no longer tolerable now that the State is no longer exclusively Anglican. The best thing to preserve the Church from the corrupting influence of a secular State is therefore to « unnationalize » it. This disestablished Church would be at once Catholic and dependent on the people for its support.